In response to Mutti et al. 2024 commentary on “Transient intracranial pressure elevations (B waves) associated with sleep apnea: the neglected role of cyclic alternating pattern” - Casper Schwartz Riedel (Fluids and Barriers of the CNS)
Abstract The physiology of transient intracranial pressure (ICP) elevations (B waves), remains incompletely understood and appears to involve multiple mechanisms, including obstructive sleep apnea (OSA). Transient ICP elevations are associated with OSA and cyclic alternating pattern (CAP) metrics, suggesting a complex interplay between sleep fragmentation and ICP dynamics. Additionally, CAP metrics could complement standard OSA assessments, providing deeper insights into transient ICP fluctuations, particularly in conditions like normal-pressure hydrocephalus and idiopathic intracranial hypertension. Future studies should explore CAP-ICP interactions to elucidate their physiological and clinical implications.